The Effect of Training Using Innovative Start Apparatus for Developing 100m Running Achievement for Runners Under 20 years - Hussein, Hassnein; Jawad , Zaidoun (Journal of Physical Education, 2022)
The importance of the research lies in manufacturing innovative apparatus for developing achievement in runners because this apparatus develops the event’s requirements of high speed and strength from the moment of first step out of the starting block. The researchers notice weakness in 100m running achievement in Iraqi runners during the first phases of the race till reaching maximal speed thus resulting in loss of time and eventually losing the race. The research aimed at designing an innovative apparatus for developing 100m running achievement for runner under 20 years old as well as identifying the effect of training using this apparatus for developing achievement. The researchers used the experimental method on the eight first champions of Iraqi Athletics championship (2021) four runners were selected for pilot study, eight as the subjects of the study to conclude that using the innovative starting apparatus have a significant effect on 100m running achievement in runners under 20 years old.